Bepikir Fungsional Calon Guru MAtematika dalam Menyelesaikan Soal Pola Bilangan Non-Linier - Azizi, Musratul; Kusaeri, Al; Syawahid, M. (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This article aims to understand the functional thinking of prospective mathematics teachers in solving non-linear number pattern problems. The functional thinking process consists of the entry, attack, and review stages in solving mathematical problems. The method used in this study is a qualitative approach with a case study type, and data collection is carried out using task-based interview techniques. This study involved 18 participants from students of the Mathematics Education study program at the State Islamic University of Mataram, from 18 participants 2 participants were selected as subjects because they had the correct answers. The results of this study indicate that both prospective mathematics teachers use different representations to express their ideas and functional thinking in solving non-linear number pattern problems. They start the generalization process with the relating action, where they connect the number of towers with the number of known matchsticks. The contribution of this study provides new insights into how prospective mathematics teachers think functionally which can be the basis for developing learning strategies, more effective learning processes and preparing prospective teachers as professionals.